Pod storage time and spontaneous fermentation treatments and their impact on the generation of cocoa flavour precursor compounds. (18th November 2020) - Koné, Koumba Maï; Assi‐Clair, Brice Judicaël; Kouassi, Ange Didier Dominique; Yao, Alfred Koffi; Ban‐Koffi, Louis; Durand, Noël; Lebrun, Marc; Maraval, Isabelle; Bonlanger, Renaud; Guehi, Tagro Simplice
Summary: Most of volatile flavour compounds occurred during the cocoa postharvest operations including pod storage and fermentation whom effects on these metabolites were aimed by the present study. Three different spontaneous fermentation treatments were performed on the farm, and the main isolated yeasts were identified using PCR‐DGGE technique. Fermented cocoa beans were solar‐dried, and their flavour compounds were identified using solid phase microextraction technique–gas chromatography–mass spectrometry. The main results showed that Pichia kudriavzevii was common yeast involved in the cocoa fermentation. Thirty flavour precursor compounds grouped into six chemical families including alcohols and pyrazines were identified in raw cocoa samples. ACP showed that short durations of pod storage and fermentation promote the formation of flavour precursors of cocoa. No spontaneous cocoa fermentation treatment influenced the occurrence of aroma compounds. The generation of flavour compounds depends only on the pod storage and the fermentative microorganisms of cocoa. Abstract : Principal component analysis (PCA) showing the distribution of the detected flavour precursor compounds in the raw cocoa beans extracted from (A) 2 days and (B) 8 days of postharvest storage in the function of the fermentation time.